PERANCANGAN SISTEM INFORMASI AKADEMIK SMA PGRI PADANGAN BERBASIS WEB (Information Technology and Telematics, 2014)
Abstrak Academic information system is a system that provides information about academic data services. The existence of academic nformation system is very important in helping to provide information to students. In this case the SMA PGRI Padangan used as a place of research, because the school information system is not managed properly, making it difficult to process the existing academic data, as well as updating the teacher data, student data update, update student grades, student megupdate presence.  The purpose of this research is to simplify the current process or to update the teacher data, student data and process the student's grades, presen sisiswa, increasing keaamanan student data so that data security is guaranteed student. The application development using SDLC (System Development Life Cycle) process of learning academic information system design PGRI Padangan high school using the web-based program PHP and MySQL database storage. Keywords: web, academic information systems, SDLC, PHP, MySQL.